Legal Politics of Pancasila Ideology against Radicalism in the State of Law Enforcement - Shinta Ayu Purnamawati; Sidik Sunaryo (Muhammadiyah University Press, 2021)
Purpose of the study:This study aims to analyze the legal politics of Pancasila as an ideology to eradicate radicalism in Indonesia.Methodology:The method employed in this study is a normative legal method using statutory, conceptual, and case approaches.Results:This study found that the fundamental problem in preventing radicalism within the framework of a rule of law is the inability to comprehend (ground) the basic values of ideology and the state constitution in a complete manner (kaffah) to manage and maintain the Unitary State of the Republic of Indonesia. The isolation and divides that negate the constitutional foundation and the ideal foundation in managing and maintaining the dignity of the nation's and state's sovereignty are another form of error in guiding the steps on the journey of the nation and the Indonesian State to the gate of bankruptcy as a sovereign nation and state. Applications of this study:This research can be used by academics and practitioners in philosophical of law so that they can create an instrument to strengthen Pancasila as an ideology to combat radicalism. Novelty/Originality of this study:Legislation may not immediately have an impact on changes and habits of people's behavior. Society does not abide by the law as autonomous individuals because principally, they are all social creatures. The social structure of a living society, called semi-autonomous social fields (SASF), gives rise to external regulations (national law) that are examined and interpreted. Therefore, the result of the encounter (clash) of internal rules with external rules in society is the formulation of strategic objectives of society that are constrasting with those originally intended by legislators.